Development of Information System for Automation of the Fitness Center - R. Grigoreva, Diana; A. Gareeva, Gulnara; M. Sultanova, Aisylu (International Journal of Engineering and Technology, 2018)
In modern society, people need ease of use of information, as in recent years the volume of processed information has increased many times. The design of information systems helps to improve the storage, processing and delivery of information, creates simplicity in understanding and searching for the database stored in the system.The practical importance of developing the module of the information system is to create a module on the platform 1C: Enterprise 8.3, which will enable the "Collection of data on potential customers". The developed module of the automated system provides an opportunity to take into account entering data on potential customers and services provided to them.Modern business technologies are characterized by high dynamism associated with the constantly changing needs of the market, the orientation of production of goods and services to the individual needs of customers and customers, continuous improvement of technical capabilities and strong competition. In these conditions, the management of enterprises is shifting the emphasis from managing the use of individual resources to the organization of dynamic business processes.In computer science, the concept of "system" is widely distributed and contains many meanings. Most often it is applied according to a set of technical tools and projects. The system can be referred to as the hardware part of the computer. The system can also be considered a large number of projects for the purpose of solving applications, supplemented with procedures for document management and calculation management.The general structure of the information system can be considered as a set of subsystems regardless of the scope of application. In this case, they speak about the structural sign of classification, and the subsystems are called providing. Thus, the structure of any information system can be represented by a set of providing subsystems.Â Â